2016
DOI: 10.1017/s1751731116000872
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Pre- and postnatal adipose tissue development in farm animals: from stem cells to adipocyte physiology

Abstract: Both white and brown adipose tissues are recognized to be differently involved in energy metabolism and are also able to secrete a variety of factors called adipokines that are involved in a wide range of physiological and metabolic functions. Brown adipose tissue is predominant around birth, except in pigs. Irrespective of species, white adipose tissue has a large capacity to expand postnatally and is able to adapt to a variety of factors. The aim of this review is to update the cellular and molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…Domestic pig (Sus scrofa) is considered as an attractive large animal model for studies on human obesity in terms of similarities found at the anatomical, physiological, pathological, and genomic levels (Spurlock and Gabler 2008;Stachowiak et al 2016). Knowledge on cellular and molecular mechanisms associated with adipose tissue development is also needed as far as pig production is concerned, since it may affect neonatal survival, postnatal growth efficiency, and health (Louveau et al 2016). Moreover, this species has also been recognized as a model organism for interphase genome organization (Foster et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic pig (Sus scrofa) is considered as an attractive large animal model for studies on human obesity in terms of similarities found at the anatomical, physiological, pathological, and genomic levels (Spurlock and Gabler 2008;Stachowiak et al 2016). Knowledge on cellular and molecular mechanisms associated with adipose tissue development is also needed as far as pig production is concerned, since it may affect neonatal survival, postnatal growth efficiency, and health (Louveau et al 2016). Moreover, this species has also been recognized as a model organism for interphase genome organization (Foster et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…From a production standpoint, not all the depots have the same value, with the depositing of IM fat, or marbling, being desirable because of its beneficial effects on sensory attributes and hence its decisive role in determining meat quality [21]. In contrast, the accumulation of excess fat in certain depots has an adverse effect by increasing production costs while decreasing product quality [15,22]. For instance, visceral fat is mostly discarded at slaughter, while an excess of SC fat lowers the commercial value of carcasses.…”
Section: Adipose Depots In Domesticated Animalsmentioning
confidence: 99%
“…The adipocytes in white adipose tissue are ordinarily large (in cattle they can reach sizes of up to 180 μm in diameter) [12], and they have few mitochondria, their cytoplasm being almost entirely taken up by a single fat vacuole [13,14]. In addition to its endocrine function, this fatty tissue subtype also plays a structural role, providing mechanical support and protection for certain parts of the body [3,15,16].…”
mentioning
confidence: 99%
“…Thereafter adipose tissue is central to energy metabolism and developmentally programmed alterations in adipose tissue physiology are considered a common phenotypic feature underlying a range of issues that become apparent in postnatal life [3]. In humans these include metabolic, cardiovascular and reproductive disorders [4][5][6], while in meat producing species excess body fat negatively impacts meat quality and hence financial returns to the producer [7,8].…”
Section: Introductionmentioning
confidence: 99%